2013
DOI: 10.1002/bit.24857
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of an alcohol dehydrogenase from Ralstonia sp.

Abstract: Stereoselective reduction towards pharmaceutically potent products with multi-chiral centers is an ongoing hot topic, but up to now catalysts for reductions of bulky aromatic substrates are rare. The NADPH-dependent alcohol dehydrogenase from Ralstonia sp. (RADH) is an exception as it prefers sterically demanding substrates. Recent studies with this enzyme indicated outstanding potential for the reduction of various alpha-hydroxy ketones, but were performed with crude cell extract, which hampered its detailed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 23 publications
2
63
1
2
Order By: Relevance
“…During this process problems with precipitation were encountered, but these were successfully addressed through the inclusion of Ca 2+ ions, 500 mM sodium chloride and glycerol in the cell resuspension and protein purification buffers (see Experimental Section). Gel filtration studies on the protein derived in this way were suggestive of a tetramer of RasADH monomers in solution, rather than the trimer suggested by earlier studies [9].…”
Section: Structure Of Rasadhsupporting
confidence: 48%
See 2 more Smart Citations
“…During this process problems with precipitation were encountered, but these were successfully addressed through the inclusion of Ca 2+ ions, 500 mM sodium chloride and glycerol in the cell resuspension and protein purification buffers (see Experimental Section). Gel filtration studies on the protein derived in this way were suggestive of a tetramer of RasADH monomers in solution, rather than the trimer suggested by earlier studies [9].…”
Section: Structure Of Rasadhsupporting
confidence: 48%
“…The model suggest that while the flexible alkyl chain of 1 can be accommodated in the distal region of hydrophobic tunnel through contortion in RasADH, less flexible substituents, such as aromatics, would not be accommodated. This is supported by substrate specificity studies [9], which show that compounds such as benzoin are poor substrates for RasADH. For SyADH, however, the larger distal portion of the hydrophobic tunnel may allow for the accommodation of such bulky groups.…”
Section: Modelling Bulky-bulky Ketones In the Active Sitesmentioning
confidence: 74%
See 1 more Smart Citation
“…The native-PAGE and HPLC analyses indicated that the enzyme was composed of 4 monomeric subunits. This is different from all currently reported higher alcohol-reducing enzymes that typically have subunits that have dimolecular weights of 26–80 kDa (Kataoka et al 2006; Kulig et al 2013; Yamada-Onodera et al 2007). By examination of the phylogenetic tree of the NAD(P)-dependent ADH family of proteins and related amino acid sequences in the existing protein database (NCBI) (Jeon et al 2008), the G. candidum S12 GDH obtained in this study may exhibit alcohol dehydrogenase and GDH (EC1.4.1.3) activity for activity towards glutamate and higher alcohols, respectively.…”
Section: Discussioncontrasting
confidence: 76%
“…Conversely, the ADH from Ralstonia sp. [22,23] ( Table 1, Entry 1) afforded the desired (S) product with moderate yield (54 % on [a] Conditions: 10 mg of lyophilized biocatalyst, glucose dehydrogenase (1 mg mL -1 ), 20 mM glucose, 0.5 mM NADH, 0.5 mM NADPH, 10 mM substrate in 500 μL reaction mixture Tris-HCl buffer pH 7.5/2-propanol (90:10, v/v), 30°C, 120 rpm in a thermoshaker for 20 h. Conversion (i.e., consumption of substrate) and product yield (i.e., formation of 1) were determined by HPLC analysis on an achiral stationary phase by using calibration curves for 1 and 2. [a] Conditions: 10 mg of freeze-dried E. coli cells containing the recombinant ADH, glucose dehydrogenase (1 mg mL -1 ), 20 mM glucose, 0.5 mM NADH, 0.5 mM NADPH, 10 mM substrate in 500 μL reaction mixture Tris-HCl buffer pH 7.5/2-propanol (90:10, v/v), 30°C, 120 rpm in a thermoshaker for 20 h. Conversion (i.e., consumption of substrate) and product yield (i.e., formation of 1) were determined by HPLC analysis on an achiral stationary phase by using calibration curves for 1 and 2.…”
Section: Resultsmentioning
confidence: 98%